Tumor Angiogenesis: Taking aim at Sox18 - Kim, Injune; Koh, Gou Young (eLife, 2017)
A small molecule called Sm4 can disrupt interactions involving a transcription factor called Sox18, while having little impact on other members of the SoxF family.
Keywords: small molecules; transcription factors; protein-protein interactions; tumour angiogenesis; gene expression